The use of OSCE (Objective Structured Clinical Examination) as an assessment tool--initial experiences at the University of Malaya - Tan, C.P.L.; Pendek, Rokiah (Malaysian Medical Association, 2005)
Formative and summative student assessment has always been of concern to medical teachers, and this is especially important at the level of graduating doctors. The effectiveness and comprehensiveness of the clinical training provided is tested with the use of clinical cases, either with real patients who have genuine medical conditions, or with the use of standardised patients who are trained to simulate accurately actual patients. The Objective Structured Clinical Examination (OSCE) is one method of assessing the adequacy of clinical skills of medical students, and their level of competence. It can be used to test a variety of skills such as history taking (communication and interpersonal skills) and performing aspects of physical examination, undertaking emergency procedures, and interpreting investigational data. It can also be used to ensure an adequate depth and breadth of coverage of clinical skills expected of a graduating doctor.